Comparison of gravimetric, creamatocrit and esterified fatty acid methods for determination of total fat content in human milk. (15th February 2017) - Du, Jian; Gay, Melvin C.L.; Lai, Ching Tat; Trengove, Robert D.; Hartmann, Peter E.; Geddes, Donna T.
Highlights: First study comparing gravimetric, esterified fatty acid and creamatocrit measurement of human milk fat. The creamatocrit measurements were closer to the standard gravimetric method. Creamatocrit method was more accurate and reproducible than esterified fatty acid method. Abstract: The gravimetric method is considered the gold standard for measuring the fat content of human milk. However, it is labor intensive and requires large volumes of human milk. Other methods, such as creamatocrit and esterified fatty acid assay (EFA), have also been used widely in fat analysis. However, these methods have not been compared concurrently with the gravimetric method. Comparison of the three methods was conducted with human milk of varying fat content. Correlations between these methods were high (r 2 = 0.99). Statistical differences ( P < 0.001) were observed in the overall fat measurements and within each group (low, medium and high fat milk) using the three methods. Overall, stronger correlation with lower mean (4.73 g/L) and percentage differences (5.16%) was observed with the creamatocrit than the EFA method when compared to the gravimetric method. Furthermore, the ease of operation and real-time analysis make the creamatocrit method preferable.